EKRANISASI NOVEL IMPERFECT KARYA MEIRA ANASTASIA KE FILM IMPERFECT KARYA ERNEST PRAKASA - Aco, Jumadin; Juanda, Juanda; Faisal, Faisal (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2021)
This study aims to describe the reduction, addition and change of variations of Meira Anastasia's Imperfect Novel to Ernest Prakasa's Imperfect Film. The research method used is a descriptive qualitative research method. The data sources in this research are the Novel Imperfect by Meira Anastasia and the Film Imperfect by Ernest Prakasa. The results of this study indicate that there are reductions, additions and changes in variations that occur in the characters, plots and settings in the novel Imperfect by Meira Anastasia to the Film Imperefect by Ernest.